The Effect of Organizational Commitment and Supervision on OHS Culture with OHS Risk Perception as an Intervening Variable at PT.PLN (Persero) ULP Tanah Jawa - Winda Chairany; Hernawaty (CV. Doki Course and Training, 2026)
This study aims to analyze the effect of organizational commitment and supervision on occupational safety and health (OSH) culture with OSH risk perception as an intervening variable among employees of PT PLN (Persero) ULP Tanah Jawa. This research employed a quantitative approach using a survey method. The population consisted of all employees, with a total sample of 57 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that organizational commitment has a positive and significant effect on OSH culture and OSH risk perception. Supervision has a positive and significant effect on OSH risk perception but does not have a significant direct effect on OSH culture. Furthermore, OSH risk perception has a positive and significant effect on OSH culture. In addition, OSH risk perception is proven to mediate the effect of organizational commitment and supervision on OSH culture. These findings indicate that improving OSH culture at PT PLN (Persero) ULP Tanah Jawa should focus on strengthening organizational commitment, enhancing consistent supervision, and increasing employees' OSH risk perception.